Spatial and temporal analysis of the COVID-19 incidence pattern in Yazd province, Central part of Iran (February 2020 to January 2021) - Farzan Madadizadeh; Seyed Yaser Ghelmani; Tahare Fallah Tafti (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Yazd province is the center of Iran and the highway for travelers to other cities. This province is susceptible to disease transmission in Iran. This study aimed to spatial analysis of corona virus prevalence, predicting the spread and determination of hot spot areas in Yazd province, central part of Iran. Methods: This analytical Cross-sectional study was conducted in Yazd province from February 2020 to January 2021. Patients with COVID-19 admitted to hospitals in Yazd province were selected by census. Required information includes the number of patients as well as their place of residence were collected through the hospital information system (HIS) of Shahid Sadoughi Hospital in Yazd, Iran. The inclusion criteria were positive polymerase chain reaction (PCR) test for COVID-19 and registration of patient information in the hospital emergency department. After collecting the data, it was entered into the ArcGIS software is 9.3.1. software. Moran's I measure and chi square test were used to data analysis. Significant level were considered 5 %. Results: Overall disease prevalence in Yazd province was equal to 0.0053. The prevalence of disease was higher in men women (55.7%, 3412 cases). The highest prevalence of the disease occurred in Yazd city (0.0096) and the highest death occurred in Meybod city (20.8%). Bahabad city also had the highest number of transfer (2.7%). Areas one (15.2% and 932 patients) and two (15.9% and 975 patients) of Yazd city were the most infected areas. There was no significant spatial pattern between the prevalence of the disease in the cities (Moran's Index: 0.18, P-value = 0.58). Conclusion: There was no spatial pattern in the prevalence of the disease and only in the city of Yazd, regions one and two need the special attention of policymakers.